Strategies Of Islamic Religious Education Teachers In The Use Of Tajwid Archer Educational Game Media As A Companion Media For Tajweed Learning - Diki Kurnia; Fahmi Maulana; Siti Khurota A’yunin (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study aims to examine the strategies of Islamic Religious Education teachers in utilizing the Tajwid Archer educational game as a supporting medium in teaching tajwid at SMP Negeri 1 Kebonagung, Pacitan Regency. This research focuses on analyzing teachers' strategies at all stages of planning, implementation, and evaluation, as well as identifying supporting and inhibiting factors that affect the integration of digital game-based media in tajwid learning. This study uses a descriptive qualitative approach with a case study design. Data were collected through classroom observations, structured interviews, and documentation involving Islamic Religious Education teachers, students, and principals. The validity of the data is ensured through source triangulation and triangulation techniques to obtain credible and systematic findings. The findings reveal that teachers apply structured strategies in three main stages. In the planning stage, the teacher harmonizes the tajwid material, especially the rules of nun sukun and mim breadfruit with interactive game features and technical and pedagogical aspects prepared. In the implementation stage, teachers integrate conceptual explanations with game-based practices, encouraging active participation, motivation, and independent learning. At the evaluation stage, teachers conduct reflective assessments through score monitoring, oral questions, and feedback, which show an improvement in students' understanding of tajweed rules and their learning engagement. Supporting factors include teachers' digital competence, institutional support, and adequate facilities, while inhibiting factors include administrative constraints, uneven device ownership, and internet dependence.